Probing CO2 reaction mechanisms and effects on the SrNb0.1Co0.9−xFexO3−δ cathodes for solid oxide fuel cells - Zhu, Y.; Sunarso, J.; Zhou, W.; Shao, Zongping (Elsevier, 2015)
Solid oxide fuel cell (SOFC) can convert chemical to electrical energy with high efficiency and low emission. In addition to the efforts to lower the operating temperature of SOFC to below 650 °C, the availability of CO2 resistant-cathode materials is envisioned to increase the practicality of the device for dual-chamber SOFC application using ambient air and also for single-chamber SOFC application using hydrocarbons. In this work, we evaluate CO2 resistance of SrNb0.1Co0.9−xFexO3−δ (x = 0, 0.1, 0.2, 0.3, 0.5 and 0.9) and the reaction mechanisms using complementary characterization techniques, e.g., powder X-ray diffraction (XRD), Fourier transform-infra red (FT-IR) spectroscopy and CO2-temperature programmed desorption (CO2-TPD). Increasing amount of Fe on the perovskite lattice resulted in the increased resistance (less sensitivity) to CO2 as reflected by less change in area specific resistance (ASR) values after CO2 exposure. The trend can be rationalized by the increase in the average metal-oxygen bond energy (ABE) imparted by the stronger Fe O bond (relative to Co O bond). Powder XRD could not detect the presence of carbonate phase on all compositions after 1 h of CO2 exposure at 600 °C.After pro-longed exposure, up to 60 h, SrCO3 was found on SNCF0.1 while remained absent on SNC. FT-IR spectra showed the evidence of carbonate vibrations only for SNCF0.1, SNCF0.2 and SNCF0.3. The appearance of an extra peak for these compositions on their CO2-TPD profiles is likely related to the carbonate decomposition which was not observed on SNC, SNCF0.5 and SNF profiles. These complementary data led us to conclude two different mechanisms i.e., CO2 adsorption accompanied by formation of strontium carbonate occurred on SNCF0.1, SNCF0.2 and SNCF0.3 whereas only CO2 adsorption occurred on SNC, SNCF0.5 and SNF. The higher oxygen non-stoichiometry for the former three compositions (with respect to the latter three compositions) correlates with the tendency to form carbonate, suggesting that oxygen vacancies can promote the formation of carbonates.